Coexistence and Confrontation of Agricultural and Food Models A New Paradigm of Territorial Development? - Gasselin, Pierre; Lardon, Sylvie; Cerdan, Claire; Loudiyi, Salma; Sautier, Denis (Dordrecht : Springer Netherlands : Imprint: Springer, 2023)
This book analyses situations of coexistence and confrontation of agricultural and food models according to four major dimensions of territorial development: the tension between specialisation and diversification; innovation; adaptation; and food transition. New agricultural and food models are being deployed in territories around the world in response to criticisms of the old forms of agriculture and food production, and in order to meet new challenges. These models embody archetypes of the observed diversity, actors' projects or new norms. A number of conceptual studies and case studies from France and other countries allow us to understand the interactions between these models (confrontation, complementarity, co-evolution, hybridisation, etc.), taking us well beyond the characterisation of their diversity and the evaluation of their relative performances. The coexistence and confrontation of these models build up their capacity for radical change. The book asks original questions about the analytical framework, its methodological challenges and the expected outcomes for the support of agricultural and food development in rural and urban territories. It is intended for researchers, teachers, students and professionals interested in territorial development. Pierre Gasselin, Sylvie Lardon, Claire Cerdan, Salma Loudiyi and Denis Sautier are the scientific coordinators of this book. They are geographers and economists at CIRAD, INRAE and VetAgro Sup, where they conduct research on the transformation of agriculture, food systems and territories in France and other countries. This book is the result of a collective research process involving 36 authors from Argentina, Belgium, Brazil, Burkina Faso, France, Japan, Switzerland and Vietnam. Jan Douwe van der Ploeg, author of the Foreword, is Professor Emeritus of Rural Sociology at Wageningen University & Research in the Netherlands and Associate Professor of Agricultural Sociology at the China Agricultural University in Beijing. He has conducted extensive research on processes of agricultural transition and on dynamics of rural development.
Preface - A courageous and truly necessary work -- General introduction - Questions, issues and analytical framework -- PART I. SPECIALIZATION/DIVERSIFICATION -- Introduction - Productive and territorial specialization: a blocking factor or a resource -- 1. From agro-industrial specialization to the plurality of models in southern Brazil -- 2. The construction of development itineraries in dairy basins, between specialized and diversified models -- 3. Does the evolution of agricultural production models allow for their coexistence in the territories -- PART II. INNOVATION -- Introduction - Innovation: ferment and fruit of the coexistence and confrontation of agricultural and food models -- 4. Mass retailing, a driving force for hybridization and innovation in territorial food systems -- 5. Coexisting in Cuma: cooperation between heterogeneous farmers -- 6. Emergence and compartmentalization of advisory subsystems for ecological intensification of agriculture in Burkina Faso -- PART III. ADAPTATION -- Introduction - Adaptation: necessity and project in coexistence -- 7. ProHuerta: from subsistence self-production to the agroecological challenge of giants -- 8. Hybridization of food chains in peri-urban production systems: the example of Pisa, Italy -- 9. Tradition in the market: valuing the know-how and identity of the Faxinal Emboque community in Brazil -- 10. History and coexistence of agricultural development models. The cases of Argentina, France and Brazil -- PART IV. TRANSITION -- Introduction - Thinking about transitions through the coexistence and confrontation of agricultural and food models: scales, actors and territorial trajectories -- 11. The role of interactions between organic and "conventional" in the ecological transition of the territorial food system of southern Ardèche -- 12. Challenging and caring: forms of solidarity in local purchasing groups -- 13. Governing coexistence in an economy "in transition": peasant farming and mega-farms in the Vietnamese dairy sector -- 14. Thinking about the diversity of transition trajectories -- PART V. A NEW PARADIGM OF TERRITORIAL DEVELOPMENT? -- Introduction - Ambivalence of models and the challenge of territorial governance of coexistence -- 15. Coexistence as an arrangement: the multiplicity of dairy models in Switzerland -- 16. Neoliberalization of agricultural policy in Japan and contradictions between agricultural models -- 17. Where is the development model of food systems that emerged at the end of the 20th century going -- 18. Agricultural and food models: don't believe in them too much, but believe in them anyway -- 19. Confronting models: coexistence to navigate between the naivety of consensus and the violence of polarization -- 20. Governing the coexistence and confrontation of agricultural and food models in the territories: paradigm, postures, methods -- List of authors.
Keywords: Agriculture; Agriculture -- Economic aspects; Economic geography; Agriculture; Agricultural Economics; Economic Geography